2020
DOI: 10.1186/s13063-020-04686-4
|View full text |Cite
|
Sign up to set email alerts
|

Tailored implementation of internet-based cognitive behavioural therapy in the multinational context of the ImpleMentAll project: a study protocol for a stepped wedge cluster randomized trial

Abstract: Background Internet-based Cognitive Behavioural Therapy (iCBT) is found effective in treating common mental disorders. However, the use of these interventions in routine care is limited. The international ImpleMentAll study is funded by the European Union’s Horizon 2020 programme. It is concerned with studying and improving methods for implementing evidence-based iCBT services for common mental disorders in routine mental health care. A digitally accessible implementation toolkit (ItFits-toolki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 56 publications
0
57
0
Order By: Relevance
“…There was also a good geographical representation of services across both Albania and Kosovo. The findings of our study provide a unique contribution to the literature in relation to the barriers and facilitators for implementing iCBT in these regions and can be used to develop context-specific solutions for implementing iCBT [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was also a good geographical representation of services across both Albania and Kosovo. The findings of our study provide a unique contribution to the literature in relation to the barriers and facilitators for implementing iCBT in these regions and can be used to develop context-specific solutions for implementing iCBT [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative focus group discussions (FGDs) were conducted with mental health care stakeholders involved on the ImpleMentAll study, a multinational trial funded by the European Union’s Horizon 2020 program. The project aimed to (1) develop and apply tailored implementation strategies for implementing evidence-based iCBT services for common mental disorders in routine mental health care through and (2) conduct a stepped wedge-cluster randomized trial to investigate the effectiveness of tailored implementation, when compared to implementation as usual (more information about the trial can be found in the trial protocol by Bührmann and colleagues [ 17 ]). Participants were recruited from 7 CMHCs across Albania (located in Tirana, Shkoder, and Korce) and Kosovo (Prizren, Gjilan, Prishtine, and Mitrovice).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To generate internationally comparable research results and facilitate multi-country studies and cross-border initiatives (Bührmann et al, 2020), translating reliable and valid instruments into languages other than English is essential (Schweizer, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The authors recommend that implementation practitioners consider such determinants to achieve better implementation results and use these to design and apply specific implementation activities. The research project ImpleMentAll aims to find evidence for such an intervention (the ItFits-toolkit) through the development, application, and evaluation of tailored implementation strategies in ongoing eHealth implementation initiatives [68].…”
Section: Principal Findings and Comparison With Prior Workmentioning
confidence: 99%